Nursing care of a patient with intracerebral hemorrhage due to ruptured cerebral arteriovenous malformation and neurogenic pulmonary edema (1例脑动静脉畸形破裂出血并发神经源性肺水肿患者的护理) - CAO Xiumin (曹秀敏); TANG Dongmei (唐冬梅) (中西医结合护理)
This paper summarized the nursing management for a patient with intracerebral hemorrhage due to ruptured cerebral arteriovenous malformation and neurogenic pulmonary edema. Based on the monitoring of postoperative vital signs of the patient, efforts were made in the following aspects: Early identification and intervention on normal perfusion pressure breakthrough syndrome; Ensuring the effective cerebral perfusion pressure during control of blood pressure and intracranial pressure; Early identification and nursing of neurogenic pulmonary edema; Enhancing the postoperative airway, fluid and volume management; Providing lung protective ventilation strategy; Carrying out awakenings and awareness recovery for the patient with chronic disorders of consciousness. (本文总结1例脑动静脉畸形破裂出血并发神经源性肺水肿患者的护理体会。术后在严密监测神志、瞳孔、生命体征变化基础上, 对正常灌注压突破综合征进行早期识别及干预, 在控制性降压及颅内压的同时保证有效的脑灌注压; 做好神经源性肺水肿的早期识别及护理, 在扩容的同时预防肺水肿进一步加重; 做好患者的呼吸道管理及容量管理, 给予正确的肺保护通气策略, 细化出入量; 对慢性意识障碍进行促醒康复, 促进患者早日康复。)